Continuous Flat Pressing of MDF Quality Control Model Framework and Collaborative Programming Approach Based on Wood Fiber Hot Pressing Mechanism - Lv, Yunlei; Liu, Yaqiu; Jing, Weipeng (Frontiers in Plant Science, 2022)
The increasing demand for limited forestry resources is driving a need to develop smarter system for saving, protection, utilization of forest and agile production. Taking the continuous hot-pressing process of wooden Medium-Density fiberboard (MDF) as the research object, and aiming at the automatic quality control of the continuous flat pressing process, the conceptual digital twin modeling for mechanism and sequence parameter control is carried out based on the cellular automata theory. A distributed coordination mode framework is constructed, and craft control programming method is proposed for the quality control of MDF continuous flat pressing. Based on the MDF continuous flat press craft mechanism and control standards a framework of five distributed flat press cooperative control mode elements for the cylinder array of continuous panel system (CPS) is defined; In order to satisfy the distributed distance servo and pressure servo demands required for multi-stage hot pressing craft design, 5 kinds of synergy collaborative control modes of multiple rack groups are constructed by mode elements; For the four types of typical deviations in slab production, such as thickness, slope, depression and bump, a multi-zone mutual cooperative mode craft control sequence is programmed. According to the type and intensity of real-time deviation, the corresponding regulation sequence is responded, which effectively solves the deviation quality control problem caused by the uncertainty interference formed by the multi-field coupling effect in actual production. The applications tests show that the adjustment and response time of the continuous flat press is greatly improved, and the quality superiority rate is controlled above 95%, which confirms the effectiveness of the control strategy.